Comparison of gaharu (Aquilaria Malaccensis) essential oil composition between each country - Nurdiyana, Abu Bakar Sidik (2008)
Aquilaria is an evegreen tree growing up to 40 meters high and 60 centimetres in diameter. These trees frequently become infected with a fungus and begin to produce an aromatic resin commonly called Aloeswood, Agarwood and Oud. The resin is created in response to an attack from Phialophora parasitica, which is a parasite fungus or mold. The purpose of this project were to know the compounds in essential oil from gaharu that been produced by hydrodistillation, to analyse of the compound in the gaharu essential oil and to determine the quality, chemical compound and method use to extract the essential oil of gaharu between different origins. Chemical compound of an agarwood originating from agarwood (Aquilaria sp. probably A. malaccensis) were investigated by GC-MS. The differences in chemical composition between the agarwood in four difference countries are discussed. The samples are taken from gaharu production industry at Kelantan, China, India and Thailand. The extraction of gaharu essential oil also been done by using hydrodistillation. Firstly preparations of the sample were done by make the sample to the sawdust and after that soak it with water. Then setting the hydrodistillation set and heated up the sample that was soaked before. The temperature of the sample was maintained at 980C to 990C for three days. Collect the sample that diluted in solvent of ethyl acetate (EtOAc) and put it in sample bottle. Cleaned the sample from the water existed, before analyze it with GC-MS. The data from GC-MS were recorded in the understandable way. The compound between the four countries have large dissimilar, but it still some component is comparable between each country. The essential oil had been produced and been analyzed. If look from analysis result, component from oil sample of industry and laboratory were not identical.